Clefts of primary and secondary palate: a review of history and of cases seen from 2001 to 2005 (2006)
The management of the cleft of the primary and secondary palate is interdisciplinary. It is complex endeavor requiring coordinated expertise of several specialists in various disciplines. We reviewed 62 patients with cleft of the primary and or the secondary palate managed between January 2001 and September 2005. The mean age at presentation was 25 months. There were 34 females (54.8%) and 28 males (45.2%). Isolated cleft of the primary palate was the most frequent accounting for 44.3%, of the patients while cleft of the primary and secondary palate was seen in 41.0%, and isolated cleft of the secondary pedate in 13.1 %. The male to female ratio in patients with isolated cleft of the primary palate (unilateral and bilateral) was 1.1 to 1, for unilateral cleft of the of the primary palate was 1.56 to 1 but all the patients with isolated bilateral cleft of the primary palate were females. The male to female ratio for patients with cleft of the primary and secondary pedate was 1 to 1 but all the patients with isolated cleft of the secondary palate were females. In cleft of the primary palate, the cleft was most frequently on the left and was complete in 63.8%. Associated malformations were seen in 11.3% of the patients, the most common being cardiac malformations We conclude that there is a need for a formation of a formal cleft team in our center to facilitate the optimum management of these patients.